2022
DOI: 10.5468/ogs.21265
|View full text |Cite
|
Sign up to set email alerts
|

Depression in pregnant and postpartum women during COVID-19 pandemic: systematic review and meta-analysis

Abstract: Coronavirus disease 2019 (COVID-19) emerged as a global pandemic in March 2020 and caused a big crisis, especially the health crisis. Pregnant and postpartum women experienced significant physical, social, and mental changes that put them at higher risk for several conditions during the pandemic. This study aimed to report the prevalence of depression in pregnant and postpartum women during the COVID-19 pandemic. Eligible studies were identified using several databases. Prevalence analysis was conducted using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…The results from this study are comparable to the results of a systematic review of 54 studies on PPD during the COVID-19 pandemic, identifying an overall prevalence of 33% [ 28 ]. These estimates are almost three times higher than the prevalence of PPD before the COVID-19 pandemic, estimated at 12% [ 29 ].…”
Section: Discussionsupporting
confidence: 83%
“…The results from this study are comparable to the results of a systematic review of 54 studies on PPD during the COVID-19 pandemic, identifying an overall prevalence of 33% [ 28 ]. These estimates are almost three times higher than the prevalence of PPD before the COVID-19 pandemic, estimated at 12% [ 29 ].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, high rates of depression (32.7%) and anxiety (26.6%) were observed in postpartum women (Mateus et al., 2022). Meta‐analytic results confirm that pregnant people and parents experienced high rates of distress (70%), anxiety (18%–42%) and depression (25%–31%) during the pandemic (Adrianto et al., 2022; Fan et al., 2021; Ghazanfarpour et al., 2022; Sun et al., 2020). Parents faced a myriad of stressors associated with school and childcare closures, working from home, and limited access to community resources during the pandemic (Patrick et al., 2020).…”
Section: Introductionmentioning
confidence: 87%
“…The COVID-19 pandemic caused unprecedented disruptions to daily life, including employment, education, health care, and social interactions. The stress of the pandemic has been associated with elevated mental health problems (i.e., depression, anxiety) across populations (Adrianto et al, 2022;Fan et al, 2021;Salari et al, 2020). Due to health care disruptions and school closures, preg-increased levels of stress among pregnant people during the COVID-19 pandemic (Lobel et al, 2022;López-Morales et al, 2021;Pope et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-pandemic epidemiological studies have shown that PND is the most common postpartum disorder among women [33], reporting a worldwide incidence ranging from 6.5% to 25.8% until 2019 [34,35]. During the COVID-19 pandemic, two recent meta-analyses [36,37] have reported prevalence rates of PND between 32.6% and 34%, evidencing a dramatic increase compared to the incidence found during the pre-pandemic period.…”
Section: Introductionmentioning
confidence: 99%